Familial Wolf-Hirschhorn syndrome resulting from a cryptic translocation: a clinical and molecular study. Issue 3 (March 1996) - Reid, E; Morrison, N; Barron, L; Boyd, E; Cooke, A; Fielding, D; Tolmie, J L
Abstract : We present three cousins who have normal karyotypes, despite having clinical features of Wolf-Hirschhorn syndrome. Fluorescence in situ hybridisation techniques confirmed that all three relatives were monosomic for the distal short arm of chromosome 4 and that a cryptic translocation involving chromosomes 4 and 11 was segregating within the family. Segregation analysis indicated that the risk of an affected child being born to a parent carrying the translocation was 15%. Molecular analysis showed that loci D4S111 and D4S115 were not deleted in the proband, thus excluding these loci from the "Wolf-Hirschhorn critical region". Surprisingly, DNA studies also suggested that the translocation breakpoint on chromosome 4 was within the region of a preexisting paracentric inversion.